THE SELECTION PROBLEMS OF ANTITHROMBOTIC THERAPY IN NONVALVULAR ATRIAL FIBRILLATION WITH COMORBIDITIES - N. A. Koziolova; Е. А. Polyanskaya (Кардиоваскулярная терапия и профилактика, 2015)
As does the clinical practice show, physician often deals with a problem of intolerability of oral anticoagulants, both vitamin K antagonists and new oral anticoagulants, either with a refuse taking these drugs at all. Hence there is an issue raises on the selection of antithrombotic therapy in atrial fibrillation (AF), and primarily, with ischemic heart disease, diabetes, stroke in anamnesis. There is a broad discussion in literature of the purpose for prescription of aspirin monotherapy to such patients with the aim of myocardial infarction and ischemic stroke prevention. In the article we present a case of female patient with nonvalvular AF having ischemic stroke and acute coronary syndrome at the background of serious comorbidities, the errors in the management are shown on the selection of antithrombotic therapy and directions provided for secondary prevention of thromboembolic complications, recurrent ischemic events according to International and Russian Guidelines.